Degree of pigmentation in composite veneers subjected to smoke from two types of cigarettes - Sandra Marcela Quisiguiña Guevara; Silvia Alexandra Reinoso Ortiz; Cristian Roberto Sigcho Romero; Brayan David Cruz Lara (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: The habit of smoking causes a huge number of conditions; one of them is the color changes in teeth and restorative materials, since the oral cavity is the most affected area when in direct contact with smoke. Objective: To evaluate the degree of pigmentation in composite veneers subjected to the smoke of two types of cigarettes. Material and Methods: An observational descriptive cross-sectional in vitro study was carried out; the sample was constituted by 20 composite veneers made with Z350 XT resin, which met inclusion and exclusion criteria and were divided into two subgroups: G1 and G2, with 10 specimens each. G1 was exposed to common cigarette smoke, while G2 was exposed to light cigarette smoke; a digital spectrophotometer (Vita Easyshade) was used to take color in three times: day 0, day 15, and day 30. Results: It was determined that the color alterations in the veneers made with 3M's Z350 XT resin exposed to light cigarette showed a greater tendency to change the tone as well as a greater convergence in the color alteration observed in the samples, taking into account that they reached a degree of saturation between 3 and 3.5 and up to 4 at the same tone level. Conclusions: Light cigarette smoke causes a more differentiated pigmentation than the common cigarette with a greater impact on saturation, which causes the samples to take a more opaque pigmentation, tending to be greyish.